De l’aurore à la nuit : le parcours du roi-soleil maya - Claude-François Baudez (Journal de la Société des Américanistes)
From dawn to darkness: the course of the maya king-sun. Carved, modeled or painted monumental images from various sites, created during the Maya Classic period, depict the main moments of the solar course in which the king is likened to the sun. These images in sequence compare the royal career to the course of the sun from dawn to darkness, and the solar cycle to the dynasty. The solar metaphor was used to legitimate the absolute power of the Maya kingship as well as to justify the necessity of dynastic continuity, while demonstrating the special relationship that existed between the king, the earth and his land.